Contributing Factors in Increasing Health Care Associated Infection (Hai’s) in Phlebitis Cases - Theresia, Siwi Ikaristi Maria; Wardani, Yulia (Department of Nursing, Faculty of Medicine, Diponegoro University, 2015)
Backgrounds: One significant problem in hospital is Health Care Associated Infection (HAI’s) and it gives many effects on patients health status.Purpose: This study was aimed to examine the incidence rate of phlebitis, the procedures of IV insertion and the factors that influence the phlebitis case in-patient department at the hospital.Methods: The main method used in this study is descriptive explorative. Started by giving training education for 15 nursing staff , medical doctor and pharmacists. Then they were obseved in doing the procedures of IV incertion, care and documentation by Using Visual Infusion Phlebitis ( VIP) scale then followed by case studies to have clear results in describing the contribution factors which influence the phlebitis incidents.Result: 35 subjects in the experimental group and 35 subjects in the control group completed The result represents that 7 from 72 patients (9,7%) were suffer from phlebitis, 25 patients (34,7%) with IV insertion were not monitored well, 5% nurses did not do the hand washing, 78% did not use the skin perlak for preventing blood to the bed linen. The mode of desinfection direction were 44% circular, 55 % from distal to proximal part, and 11% did not do the desinfectant. 100% the nurses did not documentate the IV monitoring such as the swelling, redness, the size of IV canule and any other skin symptoms of phlebitis. Some medication, insertion side of IV canule on the metacarpal area and flushing procedures were also determinant factor that lead to phlebitis cases.Conclusion: This study conclude that the treatment, care and monitoring IV insertion is a significant and important procedures to prevent phlebitis and automatically becomes an important aspect in preventing Health Care Associated Infection (HAI’s) rate in hospital.